Analysis on variable stiffness of a cable-driven parallel–series hybrid joint toward wheelchair-mounted robotic manipulator. (April 2019) - Zhang, Shan; Cao, Dongxing; Hou, Bin; Li, Shuai; Min, Hong; Zhang, Xinglei
The design of variable stiffness mechanism is of great importance to wheelchair-mounted robotic manipulators. In this article, the authors propose a cable-driven parallel–series hybrid joint toward wheelchair-mounted robotic manipulators with adjusting the system stiffness actively. The joint is a cable-driven, compression-spring-supported hybrid mechanism. Then, the kinematic analysis and cable tension analysis through static modeling are established to derive the joint stiffness model. Finally, cable-driven parallel–series hybrid joint stiffness adjustment ability analysis is carried out in four different load cases with MATLAB. Featured with light structure, stiffness adjustability, and large workspace, the proposed cable-driven parallel–series hybrid joint proves to be of great potential use for wheelchair-mounted robotic manipulators.